Ibn Jarir Al-Thabari's Interpretation of the Word “Hurun In” in the Qur'an with a Linguistic Approach - M.Agus; Andri Nirwana AN; Yeti Dahliana; Ahmad Nurrohim; Alfiyatul Azizah; Fuadi (al-Afkar, Journal For Islamic Studies, 2024)
Hurun 'in is a beauty that Allah promises to his servants as a pleasure for those who fear him. One of the pleasures that Allah promises to his servants, a companion in heaven, is the pure white angels with black eyeballs and beautiful eyes. A figure who has a beautiful nature and character that is always awake from goodness and beauty. The purpose of this study was to search for a broader meaning of the meaning of hurun 'in. In this study, the author uses the research method of tafsir maudhu'i by collecting verses in the Qur'an that have the same meaning. And then the author discusses with the tahlili method which refers to the book of tafsir ath-Tahabari by Abu Ja'far Muhammad bin Jarir Ath-Thabari. The results of this research in the view of Abu Ja'far Ath-Thabari the author found several meanings of hurun 'in his tafseer in interpreting the verses of hurun 'in.